2007
DOI: 10.1021/jm0700924
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of 6-Phenylpurine Inhibitors of Protein Kinase B through Structure-Based Design

Abstract: 6-phenylpurines were identified as novel, ATP-competitive inhibitors of protein kinase B (PKB/Akt) from a fragment-based screen and were rapidly progressed to potent compounds using iterative protein-ligand crystallography with a PKA-PKB chimeric protein. An elaborated lead compound showed cell growth inhibition and effects on cellular signaling pathways characteristic of PKB inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 24 publications
(57 reference statements)
1
59
0
Order By: Relevance
“…The first approach involves screening direct binding inhibitors targeted to the ATP binding site of Akt. Example compounds include GSK690693 (51), 6-phenylpurines (52), and conjugates of oligoarginine peptides with adenine, adenosine, adenosine-5Ј-carboxylic acid, and 5-isoquinolinesulfonic acid (53). Although these compounds displayed strong inhibitory effects, other side effects would be expected due to non-selectivity because most kinases share a conserved amino acid sequence in the ATP binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach involves screening direct binding inhibitors targeted to the ATP binding site of Akt. Example compounds include GSK690693 (51), 6-phenylpurines (52), and conjugates of oligoarginine peptides with adenine, adenosine, adenosine-5Ј-carboxylic acid, and 5-isoquinolinesulfonic acid (53). Although these compounds displayed strong inhibitory effects, other side effects would be expected due to non-selectivity because most kinases share a conserved amino acid sequence in the ATP binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PI3K/AKT signal transduction pathway has become the focus of intense interest as a critical regulator of tumor cell survival, and a number of AKT pathway inhibitors have been disclosed with a wide variety of potencies and specificities (2,44,45). In this report, we describe the in vitro and in vivo effects of AT7867, a recently developed inhibitor of AKT and p70S6K, which has been identified using fragment-based lead discovery and structure-based design technologies (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…These fragments were validated by structural studies and rapidly transformed into potent lead compounds using structure-based design to increase the efficiency of the medicinal chemistry. This research was recently described in detail and has identified potent, low molecular weight inhibitors of AKT that exhibit drug-like properties (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…[85,[88][89][90][91][92][93] Suzuki couplings have been used to introduce various substituted aryl groups into purine systems. [89,94] However, unprotected halo-9H-purine bases proved to be unreactive in common cross-coupling protocols, due to removal of the N9 proton.…”
Section: Suzuki Cross-coupling Of N-heterocyclesmentioning
confidence: 99%